1994
DOI: 10.1093/hmg/3.10.1775
|View full text |Cite
|
Sign up to set email alerts
|

The phospholipase C β3 gene located in the MEN1 region shows loss of expression in endocrine tumours

Abstract: Oncogenesis of tumours related to multiple endocrine neoplasia type 1 (MEN1) is associated with somatic deletions involving the MEN1 locus, suggesting inactivation of a tumour suppressor gene in this region. Identification of meiotic cross-overs in MEN1 families has placed the MEN1 locus centromeric of D11S807. An extended deletion mapping was performed in 27 primary parathyroid tumours, and identified D11S427 as the closest centromeric flanking marker. Through physical mapping using newly isolated cDNA clones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 0 publications
0
33
2
Order By: Relevance
“…However, the D11S807 STS isolated from the end of the D11S807 containing cosmid cCLGW39 also maps to J1-11, a short arm containing somatic cell hybrids, as well as to the RRH cell hybrids 3A1, 7C1, 2C2, and 33B1. This result is in disagreement with the previously reported placement by pulsed field gel electrophoresis (PFGE), which suggested that D11S807 is within 900 kb of D11S427 (Weber et al 1994). We place D11S427 within the PYGM segregation group by RRH (D.S.…”
Section: Radiation-reduced Somatic Cell Hybridscontrasting
confidence: 99%
See 3 more Smart Citations
“…However, the D11S807 STS isolated from the end of the D11S807 containing cosmid cCLGW39 also maps to J1-11, a short arm containing somatic cell hybrids, as well as to the RRH cell hybrids 3A1, 7C1, 2C2, and 33B1. This result is in disagreement with the previously reported placement by pulsed field gel electrophoresis (PFGE), which suggested that D11S807 is within 900 kb of D11S427 (Weber et al 1994). We place D11S427 within the PYGM segregation group by RRH (D.S.…”
Section: Radiation-reduced Somatic Cell Hybridscontrasting
confidence: 99%
“…This is more than twice what was estimated by PFGE (Janson et al 1991;Tanigami et al 1992;Weber et al 1994). However, the genetic distance between PYGM and GSTP is 5 cM (Smith et al 1995a), whereas RRH mapping suggests that SEA and GSTP are separated by at least 1.6 Mb (James et al 1994).…”
Section: Contig Sizementioning
confidence: 49%
See 2 more Smart Citations
“…The mechanisms of regulation of PLCβ3 are incompletely understood despite the enzyme's importance in a variety of cellular processes [10][11][12][13][14]. Aberrancies in expression of PLCβ3 can lead to tumorigenesis [13,15,16], and PLCβ3 knockout mice show changes in μ-opioid response [12] or early embryonic lethality [17].…”
Section: Introductionmentioning
confidence: 99%